Pertumbuhan Rumput Laut Kappaphycus alvarezii Yang Dikultur Menggunakan Dua Jenis Tali Ris Dengan Kondisi Berbeda - H, Harnoto; Mudeng, Joppy D; Mondoringin, Lukas L.J.J (e-Journal BUDIDAYA PERAIRAN, 2015)
The study aimed to determine the growth of seaweed Kappaphycus alvarezii cultured using different type of rope ris with different conditions. The study was conducted over 64 days, starting on September 1 to November 3, 2014 Village Jaya Karsa, North Minahasa Regency, North Sulawesi. The experiment was designed according to 2x3 factorial experiment in a completely randomized design (CRD). Two factors were tested, namely rope ris type and conditions. Factors ris types strap consisted of two type: Monofilament nylon and Multifilament PE. Factor conditions of ris rope consisted of three levels, namely: new, used cleaned, and the former was not cleaned, so there were 6 treatments. Experiment container was floating longlines. One unit consisted of 3 longline trial. Length per longline 28.80 m, 18 pieces of string length of rope ris 1.6 m each strap was 7 point planting, planting the overall number of points 378 points planting. K. alvarezii seaweed seedlings obtained from Jaya Karsa farmers. Weighing was done 4 times, weighing early, 1 week, 2 weeks, and at the end of week 3, using a digital scale with a precision of 1 g. Accretion weight was calculated to be the absolute growth rate (g) and daily growth rate (%). The results showed that the absolute growth and the daily growth of seaweed K. alvarezii not significantly influenced by different type and condition of the rope ris. Keywords : Kappaphycus alvarezii, long line, Multifilament PE, Monofilament nylon.